Design of End-to-end Student Research Administration Application using Rapid Prototyping Method in Universitas Advent Indonesia - Pakpahan, Andrew Fernando (8ISC Proceedings: Technology, 2022)
In this study, an end-to-end student thesis research administration application is proposed, which provides a comprehensive solution to the problems of the thesis administration process at Universitas Advent Indonesia, especially in the midst of the current pandemic. The rapid prototyping method is used to ensure that the resulting application can be developed quickly while receiving input from users to improve the application according to user requirements. The development of the application was started by conducting interviews with application users, followed by making application prototypes. The application was developed using web-based technologies (PHP and VueJS); thus, the application can be accessed using a web browser. Afterward, an integration was carried out between the developed prototype and the existing campus academic system. The proposed application provides the following features: research (thesis) title submission and approval, research guidance recording, proposal seminar approval, proposal seminar scheduling, proposal seminar grade input, proposal seminar revision records, proposal seminar revision completion approval, final defense approval, final defense scheduling, final defense’s grade input, final defense revision records, final defense revision completion approval, and final thesis book bundle completion approval. Therefore, the development of the application provides an end-to-end system that is able to help the student thesis research administration process in Universitas Advent Indonesia. Keywords : information system, web application, research administration